Behavioral traits and territoriality in the symbiotic scaleworm Ophthalmonoe pettiboneae - Temir A. Britayev (Nature Portfolio, 2021)
Abstract Among marine invertebrates, polychaete worms form symbiotic associations showing a wide variety of host use patterns. Most commonly, they live solitary on hosts, likely resulting from territorial behavior, yet little is known of the precise nature of the involved interactions. Based on field and laboratory observations, we described the symbiotic association between Ophthalmonoe pettibonae and Chaetopterus cf. appendiculatus from Nhatrang Bay (Vietnam). Then, by experimentally manipulating the competitor-to-resource ratio, we analyzed symbiont behavior and we assessed whether the 1:1 uniform distribution observed in nature could be driven by agonistic territorial behavior. Hosts and symbiont populations had low densities, lacked size relationships and showed higher prevalence when denser. Symbiont behavior included territoriality, expressed through conspecific recognition and intraspecific aggressive interactions (pursuit and escaping, hiding, choosing position, aggressive fighting, and targeting a specific bite zone). Our experiments proved that territoriality led to host monopolization by a single symbiont, provided the first empirical evidence that symbiont body injuries were caused during territorial contests, and allowed us to first suggest that a marine symbiotic invertebrate may control a territory extending beyond its host, even including neighboring hosts. Overall, this is the first report of such a complex symbiotic behavior for an annelid polychaete.